TRAINING NEEDS FOR PHYSICAL EDUCATION TEACHERS IN JORDAN IN LIGHT OF THE REQUIREMENTS OF THE KNOWLEDGE ECONOMY FROM THE POINT OF VIEW OF TEACHERS THEMSELVES - MAHMOUD OBEIDAT, LUBNA; AL-MOMANI, MOHAMMAD OMAR (REVISTA EDUCACIÓN FÍSICA, DEPORTE Y SALUD, 2025)
The study aimed to identify the level of professional stress facing physical education teachers in the Hashemite Kingdom of Jordan and its relationship to the variables of gender and years of experience. A descriptive analytical approach was followed, in addition to using a questionnaire consisting of (30) items as a study tool. The questionnaire was administered to a sample of (294) male and female physical education teachers during the second semester of the 2024/2025 academic the level of professional stress among physical education teachers was moderate, with an arithmetic mean of (2.69) and a standard deviation of (0.52). Furthermore, there were no statistically significant differences in their level of professional stress attributable to the variables of gender (male, female) and years of experience (less than 10 years, more than 10 years).